Long non‐coding RNA Sox2OT promotes coronary microembolization‐induced myocardial injury by mediating pyroptosis. (18th March 2022) - Xuan, Liying; Fu, Danni; Zhen, Dong; Bai, Dongsong; Yu, Lijun; Gong, Guohua
Abstract: Objective: As a common complication of coronary microembolization (CME), myocardial injury (MI) implies high mortality. Long non‐coding RNAs (lncRNAs) are rarely studied in CME‐induced MI. Herein, this study intended to evaluate the role of lncRNA Sox2 overlapping transcript (Sox2OT) in CME‐induced MI. Methods: The CME rat models were successfully established by injection of microemboli. Rat cardiac functions and MI were observed by ultrasonic electrocardiogram, HE staining, and HBFP staining. Functional assays were utilized to test the inflammatory responses, oxidative stress, and pyroptosis using reverse transcription quantitative polymerase chain reaction, Western blotting, immunohistochemistry, immunofluorescence, and ELISA. Dual‐luciferase reporter gene assay and RNA immunoprecipitation were conducted to clarify the targeting relations between Sox2OT and microRNA (miRNA)‐23b and between miR‐23b and toll‐like receptor 4 (TLR4). Results: Rat CME disrupted the cardiac functions and induced inflammatory responses and oxidative stress, and activated the nuclear factor‐kappa B (NF‐κB) pathway and pyroptosis (all P < 0.05). An NF‐κB inhibitor downregulated the NF‐κB pathway, reduced pyroptosis, and relieved cardiomyocyte injury and pyroptosis. Compared with the sham group (1.05 ± 0.32), lncRNA Sox2OT level (4.41 ± 0.67) in the CME group was elevated ( P < 0.05). Sox2OT acted as a competitive endogenous RNA (ceRNA) of miR‐23b to regulate TLR4. Silencing of Sox2OT favoured miR‐23b binding to 3′UTR of TLR4 mRNA leading to suppressed TLR4‐mediated NFKB signalling and pyroptosis in myocardial tissues harvested from CME rat models. In addition, miR‐23b overexpression could supplement the cytosolic miR‐23b reserves to target TLR‐4 and partially reverse Sox2OT‐mediated pyroptosis in LPS‐treated H9C2 cells. Conclusions: This study supported that silencing Sox2OT inhibited CME‐induced MI by eliminating Sox2OT/miR‐23b binding and down‐regulating the TLR4/NF‐κB pathway. This investigation may provide novel insights for the treatment of CME‐induced MI.